Guided Imagery Therapy to Reduce Anxiety in Elderly Hypertension Sufferers - Hidayat, Nandita Milda; Fitriani Olivia Dewi, Nurul; Suprapti, Betty; Rismawan, Wawan; Marpatmawati, Idhfi (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
The World Health Organization in 2019 reported that approximately 1.13 billion people worldwide suffer from hypertension, meaning that 1 in 3 people globally is diagnosed with hypertension. Hypertension can cause individuals to experience anxiety, which, in turn, can worsen their condition. Therefore, hypertensive patients experiencing anxiety require appropriate and effective treatment to reduce anxiety and prevent worsening hypertension. Objective To describe the characteristics of elderly individuals experiencing anxiety, to illustrate the results of anxiety detection using the HARS method, to explain the implementation of the guided imagery technique, and to assess changes in anxiety levels among elderly hypertensive patients following guided imagery therapy. Research Method A qualitative descriptive approach with a case study method was used to explore nursing issues and client intervention techniques by applying guided imagery therapy to reduce anxiety in elderly hypertensive patients. The results is Anxiety reduction was observed after guided imagery therapy, with a decrease of 5 points in respondent 1, 3 points in respondent 2, and 6 points in respondent 3. The study concluded that after four days of guided imagery therapy, all three respondents experienced a reduction in anxiety levels. Initially, all three respondents had severe anxiety levels. After the therapy, their anxiety levels decreased to a moderate level.